2011
DOI: 10.1016/j.molcel.2010.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Chromodomain-Mediated Oligomerization of HP1 Suggests a Nucleosome-Bridging Mechanism for Heterochromatin Assembly

Abstract: Summary HP1 proteins are central to the assembly and spread of heterochromatin containing histone H3K9 methylation. The chromodomain (CD) of HP1 proteins specifically recognizes the methyl mark on H3 peptides, but the same extent of specificity is not observed within chromatin. The chromoshadow domain of HP1 proteins promotes homodimerization, but this alone cannot explain heterochromatin spread. Using the S. pombe HP1 protein, Swi6, we show that recognition of H3K9 methylated chromatin in vitro relies on a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
381
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(409 citation statements)
references
References 30 publications
27
381
1
Order By: Relevance
“…In our kinetic model, k + describes the net rate of H3K9me3 addition at nucleosomes immediately adjacent to H3K9me3-marked sites. In this way, spreading of H3K9me3 along the chromosome occurs through linear propagation of the mark to neighboring nucleosomes, consistent with proposed spreading via HP1 oligomerization (5,6,8,21,22). Mechanistically, this propagation likely requires multiple steps (e.g., recruitment of HP1, oligomerization, recruitment of HMT, enzymatic methylation, etc.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…In our kinetic model, k + describes the net rate of H3K9me3 addition at nucleosomes immediately adjacent to H3K9me3-marked sites. In this way, spreading of H3K9me3 along the chromosome occurs through linear propagation of the mark to neighboring nucleosomes, consistent with proposed spreading via HP1 oligomerization (5,6,8,21,22). Mechanistically, this propagation likely requires multiple steps (e.g., recruitment of HP1, oligomerization, recruitment of HMT, enzymatic methylation, etc.…”
Section: Resultssupporting
confidence: 78%
“…In mammalian cells, H3K9me3 is associated with heterochromatic and transcriptionally silent regions (1)(2)(3)(4). H3K9me3-based repression requires Heterochromatin Protein 1 (HP1), which mediates cis-spreading of the H3K9me3 mark by binding existing H3K9me3 sites (5-7), oligomerizing to bind neighboring nucleosomes (8,9), and recruiting H3K9-specific histone methyltransferases (HMTs) (10)(11)(12)(13) to induce outward spreading of the mark.…”
mentioning
confidence: 99%
“…Schizosaccharomyces pombe HP1 displays a 0.12 ÎŒM affinity for the H3K9me3-containing nucleosomes (24). We found that the linked PHD fingers of CHD4 bind to the unmodified H3 tails of the tetrasome with the Kds of 0.33 and 0.96 ÎŒM, and these affinities are expected to increase significantly upon methylation of Lys9 (a 10-fold increase is seen with H3 peptides alone).…”
Section: Resultsmentioning
confidence: 75%
“…Second, enzymes bound to neighboring nucleosomes can interact laterally. Canzio et al showed that the HP1 proteins can form oligomers through chromodomain and chromoshadow domain lateral interactions, and enhanced lateral interactions lead to higher percentage of H3K9me3 (31,32). Interestingly, mutations related to the histone modification enzyme lateral interactions have been reported in cancer cells (33).…”
Section: Identify Puzzle From Experimental Studiesmentioning
confidence: 99%